Adaptive shaping of laser beams for high-harmonic generation applications - BENJAMIN HEATH (2022)
This thesis explores the use of adaptive optics to create tailored laser profiles to drive the process of high-order harmonic generation (HHG).A deformable mirror controlled by a genetic, simulated-annealing algorithm (SA), and a genetic-annealing hybrid algorithm (HA) have been used to create super-Gaussian intensity profiles of orders ranging from P = 1 to P = 2 using a low-powered He-Ne laser. Between these three algorithms it was found that there is a compromise between the algorithm performance and reliability, and the algorithm complexity.Simulated super-Gaussian beam-shaping with a phase-only SLM has been performed with a SA and HA algorithm and compared to a known π-shift method. The HA has shown an improvement in super-Gaussian quality for high orders, P ≈ 2.6.Simulations of HHG driven by super-Gaussian driver fields have been made using both the simple dipole model and the strong field approximation. It has been shown that HHG beam divergence decreases with increased order P . The fringe visibility has also been calculated as a measure of coherence.